EFFECT OF TIME, MEDIA AND ROOT INDUCING AUXINS ON THE ROOTING OF GUAVA (CV. ALLAHABAD SAFEDA) AIR-LAYERS UNDER HIGH RAINFALL ZONE - KUMAR, SUDHIR; SAKTHIVEL, T.; CHITHIRAICHELVAN, R.; KARUNAKARAN, G. (Annals of Agricultural Research, 2014)
The present investigation was carried out to know the suitable time, optimum concentration of growth regulators and locally available media to get the rooting success in 12 years old guava air layers cv. Allahabad Safeda under high rainfall zone of Kodagu. Study revealed that 10,000 ppm (T4) was best among all the treatments as far as rooting is concerned. July was the best month for makingthe air layers in guava cv. Allahabad Safeda. Among the media, through no significant difference was found in respect to rooting percentage while the coffee husk (M3) gave the best result compared to other media used in the study.